2019
DOI: 10.1111/jam.14517
|View full text |Cite
|
Sign up to set email alerts
|

Implications of grey zone results for routine hepatitis C virus screening with the ARCHITECT HCV‐Ag assay

Abstract: Aims Hepatitis C virus antigen (HCV‐Ag) detection requires retesting for samples with grey zone results (GzR), adding cost and time and decreasing reliability. Our aim in this study was to evaluate the frequency and significance of GzR during the use of the automated Architect HCV‐Ag assay in routine clinical practice. Methods and Results We studied HCV‐Ag levels in 952 serum samples using the ARCHITECT HCV‐Ag assay. GzR were detected in 33 samples; 25 were reactive on retesting and 19 were anti‐HCV positive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On retesting, none of them tested negative. Previous studies have shown that gray-zone results found to be negative on retesting do not require additional confirmatory testing 33 .…”
Section: Discussionmentioning
confidence: 96%
“…On retesting, none of them tested negative. Previous studies have shown that gray-zone results found to be negative on retesting do not require additional confirmatory testing 33 .…”
Section: Discussionmentioning
confidence: 96%
“…The other 8 GzR samples were non-reactive on retesting and on HCV-RNA test. 22 No significant differences were found on comparing HCV-cAg values. This confirms that, even though GzR occur, HCV-cAg is a robust alternative to HCV-RNA detection in the active detection of infections, except in donor screening scenarios, where the use of molecular methods would be advisable.…”
Section: Hcv-cag Expression Highly Agreement With That Of Hcv-rnamentioning
confidence: 91%